Teacher Classroom Practices and English Language Reading Readiness of Children in Grade One at Kericho Rehabilitation School, Kenya (Universitas Negeri Semarang, 2022)
English Language Reading Readiness (ELRR) is a preparation of children by giving them the chance to improve their ability to listen, speak, read and write effectively, to apply the desired vocabulary, and develop the appropriate academic readiness skills. English Language Reading Readiness is of great importance in improving equity in access to learning language and education results, particularly for juvenile delinquency. Children in rehabilitation schools have a vital social issue that every nation tries to contain its control amongst the clear evidence, with the correct nurturing such that if psychotherapeutic interventions are not provided to the young offenders, they may eventually graduate to hardcore criminals. The purpose of this study was to establish the effect of teacher classroom practices on English language reading readiness of children in Grade One at Kericho Rehabilitation School, Kenya. The study objectives were: to establish the effect of teaching methodology on English Language Reading Readiness of children in Grade one at Kericho Rehabilitation School, explore the effect of instructional resources on English Language Reading Readiness of children in Grade one at Kericho Rehabilitation School, determine the effect of modeling discipline management mechanisms on English Language Reading Readiness of children in Grade one at Kericho Rehabilitation School and to determine the effect of the checklist assessment tool on English Language Reading Readiness of children in Grade one at Kericho Rehabilitation School. The study reviewed the relevant literature related to the objectives. The study was guided by Noam Chomsky’s Language Acquisition Theory of 1998 which demonstrated and illustrated the standard structural theories of language acquisition. The significance of the study was to help the Ministry of Education (MOE) to formulate and implement classroom policies for children in the rehabilitation schools. The study adopted a case study research design. Purposive sampling was used to include all the 14 children in Grade one and 4 teachers at Kericho Rehabilitation School. The respondents of the study were; all the children in Grade One, one Head teacher and four regular teachers in the school. Data was collected using pre-test and post-test, questionnaire for Head teacher and other teachers, observation schedule of live lessons, and documentary analysis. The teachers were trained on how to apply the new classroom intervention strategies namely; the phonics method, the use of resources, the modeling classroom discipline management mechanisms and the checklist assessment tool. The pre-test and the post-test were administered to the children and results computed. Data was analyzed qualitatively and quantitatively using Statistical Package for Social Sciences (SPSS) to compute t-test for establishing any statistically significant differences between the overall pre-test mean score and post-test mean scores of the uni-group. The study findings indicated that, the children’s pre-test mean score was low and there was no statistically significant difference within the group. The low pre-test performance was because the children had not acquired sufficient English language reading readiness skills due to the influence of teacher pedagogical competencies as indicated in inappropriate teaching methods, insufficient learning resources, use of inappropriate classroom discipline management mechanisms, and inappropriate classroom assessment techniques. The children’s post-test mean score for the group improved, after applying the interventions. There was, therefore, a statistically significant difference between the pre-test and post-test overall mean scores within the group due to the group having been taught using the phonics method, effective and adequate resources, the modeling discipline management mechanism and the checklist assessment method. The study concluded that; children’s English language reading readiness may have been influenced by teacher classroom practices. Children’s performance could be improved by teachers who not only applied better classroom practices, but also the skills, attitudes and motivation to use the pedagogical competencies holistically in rehabilitation schools. The study recommendations were that: The Ministry of Education needs to consider in–servicing teachers in rehabilitation schools to re-orient their classroom practices and also to consider establishing Early Childhood Development Centers within rehabilitation schools as a strategy of laying foundation to reading in Grade one. The school administrators need to support the teachers with facilities and time and also ensure that they applied better English language reading readiness skills in all their teaching. For further research, this study recommended that; research could be carried out on the influence of teacher pedagogical competencies on children’s performance in other language skills or in other subjects at any level of reading. Key Words: Rehabilitation School, Early Childhood Education, Reading Readiness, Phonics, Instruction, Modelling, Assesment Tool